SIMULATION AND ANALYSIS ON THERMAL CHARACTERISTIC OF SPINDLE REDUCER BOX OF BORING AND MILLING MACHINING CENTER - WANG ChuanYang; LIU HaiHua; QIU DeYi (Jixie qiangdu)
The 3D model of spindle reducer box of Boring and Milling Machining Center was established. The gear transmission was analyzed. The thermal load was found by calculating the heat flow of the gear and the heat generated of bearing.The calculated heat convection coefficient was defined as the boundary condition. The temperature field of the spindle reducer box was simulated. By thermal-structure coupling analysis,the thermal deformation results of the box and gears were obtained.Finally,the reliability of spindle box was verified according to the comparison of the simulation result against the nominal clearance.